Penerapan Algoritma Dynamic Programming Dalam Penentuan Prioritas Pengerjaan Tugas Kuliah Mahasiswa - Hidayat, Febrian Nur; Ferdinan, Bryan Desmonda; Saputra, Rendy; Christian, Efrans; Pranatawijaya, Viktor Handrianus (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
College assignments are an essential part of every student’s learning process. However, the multitude of tasks from various subjects often leaves students confusedabout prioritizing their work. This research aims to assist students in effectively determining the priority of completing college assignments using a dynamic programming algorithm. This research uses a modeling method of various subjects as variables with different weights, such as deadlines and task difficulty levels. The dynamic programming algorithm is then used to find the optimal solution in completing all tasks, considering various possibilities, both deadlines and difficulty levels. This research has found that the application of the dynamic programming algorithm can create the best solution that takes into account all aspects and produces optimal schedulling in completimg tasks. Althought it requires more time in the calculation process, this algorithm can also provide an optimal solution to help students complete their tasks efficiently and effectively. The application of this dynamic programming algorithm is expected to be a solution for students in completing their tasks better and avoiding stress due to task accumulation. Besides, this research also has the potential to benefit lecturers in assigning tasks to students by considering optimal capabilities and working time. Thus, this research can help improve the quality of learning in higher education.